Kant’s Criticism of European Colonialism: A Contemporary Account of Cosmopolitan Law - Sánchez Madrid, Nuria (Problemos, 2018)
[full article, abstract in English; only abstract in Lithuanian] This paper tackles Kant’s juridical arguments for criticizing European colonialist practices, taking into account some recent accounts of this issue given by Kant scholars as Ripstein, Cavallar, Flikschuh, Stilz and Vanhaute. First, I focus on Kant’s grounding of cosmopolitan union as a juridical requirement stemming of the systematic character of the rational doctrine of right. Second, I pay attention to Kant’s remarks about how the European nations ought to establish commercial relations with other nations in the world and how they should approach non-state people. I draw the conclusion that Kant’s juridical-political writings should be consider as a forerunning corpus for furthering an anti-colonialist mind in the European philosophy of Enlightenment.